Community empowerment through snakefruit diversification as fruitleather using a dough machine in the Kramat Bangkalan Village - Rosida, Dedin Finatsiyatull (Talenta Publisher Universitas Sumatera Utara, 2024)
Kramat Village is one of snakefruit plantation centre in Bangkalan Madura. Some of the processed products are produced into specific typical regional food and can be sold which lead to the improvement of the community's economy. However, in its journey, the snakefruit products are difficult to market outside the region. The purpose of this program is to create a new innovation in processing snakefruit as a culinary product and souvenir typical of Kramat Village Bangkalan. The results of the activity show that innovation in processing snakefruit into fruitleather products is quite popular and has the potential to be a superior product. The development of Kramat Village and its surroundings into a tourist village has made agrotourism actors and snakefruit processors take the initiative to develop processed snakefruit products into culinary delight of the village. However, developing processed snakefruit products into culinary and souvenirs typical of the village is not easy. It requires various kinds of knowledge ranging from processing, packaging to marketing. Empowerment program society is also done in its marketing through mentoring with improvement knowledge in digital marketing field